2020 In Review: An opportunity missed?. Issue 12 (December 2020) - Kotoulas, Yiannis
Abstract : The coronavirus pandemic has disrupted eye health initiatives in what was meant to be a seminal year for the profession. Yiannis Kotoulas reports.